Acute oxygen consumption response to fast start high-intensity intermittent exercise - Miller, P.; Perez, N.; Farrell, J. W. (Sports, 2023)
The current investigation compared the acute oxygen consumption (VO2) response of two high-intensity interval exercises (HIIE), fast start (FSHIIE), and steady power (SPHIIE), which matched w prime (W`) depletion. Eight cyclists completed an incremental max test and a three-minute all-out test (3MT) to determine maximal oxygen consumption (VO2max), critical power (CP), and W`. HIIE sessions consisted of 3 X 4 min intervals interspersed by 3 min of active recovery, with W` depleted by 60% (W`target) within each working interval. SPHIIE depleted the W`target consistently throughout the 3 min intervals, while FSHIIE depleted the W`target by 50% within the first minute, with the remaining 50% depleted evenly across the remainder of the interval. The paired samples t-test revealed no differences in the percentage of training time spent above 90% of VO2max (PT = 90% VO2max) between SPHIIE and FSHIIE with an average of 25.20% and 26.07%, respectively. Pairwise comparisons indicated a difference between minute 1 peak VO2, minute 2, and minute 3, while no differences were present between minutes 2 and 3. The results suggest that when HIIE formats are matched based on W` expenditure, there are no differences in PT = 90% VO2max or peak VO2 during each interval.